The Design and Dynamics of Performance Measurement Systems in the Public Sector - Heinrich, Carolyn J.; Marschke, Gerald R. (My University, 2008)
The authors use the principal-agent framework to synthesize theoretical and empirical knowledge of the implementation of performance management systems in the public sector. They describe a dynamic framework to account for individuals' strategic behavior over time.